The Dialectics of Islamic Religious Education Learning and the Formation of Students’ Personality from the Perspective of Islamic Tarbiyah - Basuki Basuki; Dede Ilham; Ahd. Mujahid (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
This article examines the dialectical relationship between Islamic Religious Education (PAI) learning and the formation of students’ personality from the perspective of Tarbiyah Islamiyah. The scope of the study focuses on the dynamic interaction between learning objectives, pedagogical strategies, the internalization of Islamic values, and the development of students’ Islamic personality. The study aims to analyze how PAI learning functions as an interactive educational process that goes beyond the transmission of religious knowledge to shape students’ attitudes, behaviors, and character in a sustainable manner. This study employs a qualitative literature-based approach. Data analysis is conducted using thematic analysis by reviewing, categorizing, and synthesizing key findings from relevant literature to identify patterns, concepts, and perspectives related to Islamic Religious Education, students’ personality development, and Tarbiyah Islamiyah. Literature sources are selected based on several criteria, including peer-reviewed scholarly articles published within the last five years, relevance to the research focus, and a predominance of journal articles (at least 80%), including national and international journals as well as articles from the Al-Hikmah Journal of Education. The findings indicate that PAI learning within the Tarbiyah Islamiyah framework demonstrates a dialectical nature that positions students as active subjects of education through the integration of faith (iman), knowledge (ilm), and practice (amal). Learning processes grounded in role modeling, habituation, and contextualization of values play a significant role in fostering students’ moral character, responsibility, and religious awareness. This study contributes theoretically to the discourse on Islamic education by reinforcing the strategic role of PAI in developing students’ holistic personality within the Islamic educational paradigm.